Real Options Signaling Games with Applications to Corporate Finance - Grenadier, Steven R.; Malenko, Andrey (Review of Financial Studies, 2011)
We study games in which the decision to exercise an option is a signal of private information to outsiders, whose beliefs affect the utility of the decision-maker. Signaling incentives distort the timing of exercise, and the direction of distortion depends on whether the decision-maker's utility increases or decreases in outsiders' belief about the payoff from exercise. In the former case, signaling incentives erode the value of the option to wait and speed up option exercise, while in the latter case option exercise is delayed. We demonstrate the model's implications through four corporate finance settings: investment under managerial myopia, venture capital grandstanding, investment under cash flow diversion, and product market competition.